Legislative and International Legal Features of the Environment Protection in the Arctic Zone of the Russian Federation - O. S. Rostunova (Московский журнал международного права)
The article considers questions concerning the application of Soviet, Russian nature protection legislation to the Arctic zone of the Russian Federation, the limits of this zone, and the role of the Arctic Council in the Arctic environment protection sphere.